2004
DOI: 10.1002/app.21073
|View full text |Cite
|
Sign up to set email alerts
|

Graft copolymerization of methacrylamide onto acrylic fibers initiated by benzoyl peroxide

Abstract: Acrylic fibers were graft copolymerized with methacrylamide in aqueous media, using benzoyl peroxide as a free-radical initiator. The grafting reactions were carried out within the 75-95°C temperature range, and the effect of initiator, monomer concentrations, and the amount of fiber on the graft yield were also investigated. The maximum graft yield was reached at the benzoyl peroxide concentration of 3.0 ϫ 10 Ϫ3 mol/L and the optimum temperature of 85°C. The activation energy of the reaction was found to be 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…As it is clear, it has been occurred some little changes in the morphology of the fiber but photographs demonstrated that the surface of 17.46 % poly AA-grafted acrylic fiber was as smooth and homogeneous as that of pure fiber. This can be related to lower grafting yield due to the chemically and physically bonded poly AA on the fiber [20].…”
Section: Surface Morphology Of the Ungrafted And Grafted Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is clear, it has been occurred some little changes in the morphology of the fiber but photographs demonstrated that the surface of 17.46 % poly AA-grafted acrylic fiber was as smooth and homogeneous as that of pure fiber. This can be related to lower grafting yield due to the chemically and physically bonded poly AA on the fiber [20].…”
Section: Surface Morphology Of the Ungrafted And Grafted Fibersmentioning
confidence: 99%
“…Grafting reaction was carried out by slight changes in morphological surface of fibers compared with other researches in this field [20,21] and by increasing of grafting yield increased water absorption of acrylic fibers.…”
Section: Introductionmentioning
confidence: 99%
“…BPO initiators will decompose to form radicals at a temperature of 80− 95°C. Free radicals and unpaired electrons will react with monomers to form long polymer chains [32].…”
Section: Synthesis Of the Imprinted Monolithic Columnsmentioning
confidence: 99%
“…2-thiozyl methacrylamide (TMAAm) is one of the most important vinyl monomers for large polymer-addon can be easily obtained because of the hydrophilic natüre of the TMAAm [53,54]. Poly(2-thiozyl methacrylamide), as an important industrial polymer, has some desirable properties, including, it is less toxic, polar and less expensive than other vinyl monomers [55].…”
Section: Introductionmentioning
confidence: 99%